Consumer Legal Protection Against Default in Buying and Selling E-Commerce - Budiono, Arief; Shaharani , Zahira; Prakoso, Andria Luhur (Fakultas Hukum Universitas Muhammadiyah Sorong, 2023)
Introduction: E-commerce is a modern business activity that has two properties: not meeting the parties directly (nonfice) and without the need for a genuine signature by the non-signing parties. Methodology: Type of research using normative juridical research. This study used two approaches: a state approach and a conceptual approach. The primary and secondary data are sourced by qualitative methods of data analysis and the presentation of descriptive data analysis. Results and Discussions: Act No. 19 of 2016 on ITE explains that E-commerce transactions are included in responsible transactions. The legal form of protection is listed in Article 28 (1). The settlement of E-commerce transactions in dispute is carried out using peaceful means. If the line is ineffective, the consumer may sue the owner in accordance with the contents of Article 45 of the Constitution. Conclusion: Consumer law protection has two concepts: preventive and repressive legal protection. Efforts can be completed through litigation or processing of adaptation, negotiation, mediation, conciliation and arbitration)